Field Implementation of Climate-Smart Integrated Small Ruminant Innovations (SmaRT Pack) - Haile, Aynalem; Getachew, Tesfaye; Belay, Berhanu; Rekik, Mourad; Rischkowsky, Barbara A. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Small ruminant value chain development started in Ethiopia as part of the Livestock and Fish CGIAR Research Program (CRP) in 2012 and then continued since 2017 as Livestock CRP in seven sites representing different regions of Ethiopia, production systems and communities. The initiative aimed to test technological and institutional innovations that would transform the small ruminant value chain, which involved rigorous procedures. Over the years, we have pilot-tested many innovations along the small ruminant value chain, which were found to be technically sound to be implemented, financially feasible and improved the livelihood of communities. Most of the proven technologies were also evaluated from an environmental sustainability lens focusing on sustainably increasing small ruminant productivity and incomes, adapting and building resilience to climate change and reducing greenhouse gas emissions, where possible. Therefore, we believe the technologies were ready to scale. As part of the Accelerating the Impact of CGIAR Climate Research in Africa (AICCRA), we are facilitating the scaling of these innovations through various mechanisms. One such approach is to demonstrate the framework on the ground for scaling these climate-smart small ruminant innovation packages involving research and extension systems in Ethiopia. For this purpose, we identified, through a consultative process, three sheep value chain sites (Bonga, Doyogena and Menz) and one goat (Konso) site in 2022. In each site, we selected a few villages (see the table below) where we tested the framework. Our institutional arrangement involved the establishment of a breeder/ producer cooperative for each village. More than 7500 people directly benefited from the implementation.